Comprehensive genome data analysis establishes a triple whammy of carbapenemases, ICEs and multiple clinically relevant bacteria. Issue 10 (25th October 2020) - Botelho, João; Mourão, Joana; Roberts, Adam P.; Peixe, Luísa
Abstract : Carbapenemases inactivate most β-lactam antibiotics, including carbapenems, and have frequently been reported among Enterobacteriaceae, Acinetobacter spp. and Pseudomonas spp. Traditionally, the horizontal gene transfer of carbapenemase-encoding genes (CEGs) has been linked to plasmids. However, given that integrative and conjugative elements (ICEs) are possibly the most abundant conjugative elements among prokaryotes, we conducted an in silico analysis to ascertain the likely role of ICEs in the spread of CEGs among all bacterial genomes ( n =182 663). We detected 17 520 CEGs, of which 66 were located within putative ICEs among several bacterial species (including clinically relevant bacteria, such as Pseudomonas aeruginosa, Klebsiella pneumoniae and Escherichia coli ). Most CEGs detected within ICEs belong to the IMP, NDM and SPM metallo-beta-lactamase families, and the serine beta-lactamase KPC and GES families. Different mechanisms were likely responsible for acquisition of these genes. The majority of CEG-bearing ICEs belong to the MPFG, MPFT and MPFF classes and often encode resistance to other antibiotics (e.g. aminoglycosides and fluoroquinolones). This study provides a snapshot of the different CEGs associated with ICEs among available bacterial genomes and sheds light on the underappreciated contribution of ICEs to the spread of carbapenem resistance globally.